Production of Agarwood Essential Oil: Study on Effectiveness Pre-Treatment Technique of Hydrodistillation Extraction - Yusoff, nor Atikah; Tajuddin, Saiful Nizam; Hisyam, Anwaruddin; Mohd Omar, Nor Adila (Borneo Journal of Resource Science and Technology, 2016)
There are many uses of agarwood trees in a number of countries around the world. However, lack in extraction process efficiency was affected to the lower product quality and oil yield. Therefore, this research was aimed to investigate the effect of pre-treatment techniques of soaking with water and soaking with three fungi on agarwood oil yield. The oils produced were compared with industrial samples. Analysis of chemical compounds is done by using Gas Chromatography-Flame Ionization Detector (GC-FID) and Gas Chromatography-Mass Spectrometry (GC-MS). As a result, the sample treated with fungi Phanerochaete chrysosporium achieved the highest average oil yields of 0.58% with content of 80.13% of total chemical compounds compared to sample treated with water only consist of 0.27% oil yield and 72.58% of total chemical compounds was detected. The sample soak with fungi is more advantageous than soak with water in terms of oil productivity, energy saving and efficiency process. The main component present in all parameter studied were epoxybulnesene (1.64%- 7.54%), tetradecanal (1.02%-6.10%), agarospirol (0.29%-1.34%), bulnesol (0.59%-8.07%), selina-3,11-dien-9- ol (1.10%-4.02%), oxo-agarospirol (1.12%-10.80%) and eudesmol (0.19%-9.17%).